Assessing the impacts of invasive non-native African sharptooth catfish Clarias Gariepinus - Kadye, Wilbert Takawira (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2012)
Invasive species are of particular concern as they have the potential to alter community structure and food web relationships within their invaded habitats. African sharptooth catfish Clarias gariepinus, a generalist predator, was introduced through an inter-basin water transfer scheme into the Great Fish and Sundays Rivers, Eastern Cape, South Africa, where it threatens the native riverine biota. This thesis assessed its impact from a trophic perspective. Patterns in catfish distribution and abundance revealed an upstream to downstream gradient that was associated with spatial distribution of most species within the mainstream, and a mainstream to tributary gradient that was associated with the spatial distribution of native minnows. The catfish was predicted to occur widely within the mainstem habitats and to decrease progressively along the mainstrem to tributary gradient with the physico-chemical environment being a good proxy for predicting both its occurrence and abundance. The results suggest the catfish proliferated within mainstem habitats where invasion resistance was possibly reduced due to alteration of flow. Population dynamics and size structuring of two native cyprinid minnows Pseudobarbus afer and Barbus anoplus, threatened by catfish, were examined within uninvaded headwater streams in relation to their proximate physical habitats. Their habitats were characterised by seasonal variation in physico-chemical conditions and a spatial variation in substrata compositions. No evidence of differences was found between seasons for density and capture probability for either species. The population size and density for P. afer was found to increase with increasing proportion of boulders. In comparison, B. anoplus population size and probability of capture increased with increasing proportion of bedrock and bank vegetation, respectively. Size structuring was explained predominantly by seasonality and habitat variables for P. afer and B. anoplus, respectively. Stable isotope ratios of carbon and nitrogen were used to compare the spatial variation in both the community-wide and catfish-specific niches and to estimate catfish prey sources from different habitats within the invaded systems. Aquatic community and catfish niches were statistically different among localities, suggesting that each locality had a distinct community-wide trophic structure. Dispersion metrics indicated no evidence of differences in the clustering among individuals, but provided evidence of differences in path trajectories for the comparisons of catfish populations that suggested dietary plasticity within different localities. Dietary studies revealed both ontogenetic shift and omnivory that suggested that catfish may exhibit less pronounced top-down effects within its invaded habitats. Manipulative experiments were used to test the response of benthic macroinvertebrates within two rivers that were differentially impacted by catfish as a presstype disturbance. Macroinvertebrates were non-responsive to catfish presence within a system where catfish had previously been established. In contrast, excluding catfish in this system indicated a response that suggested the importance of refuge within invaded habitats and the possible recovery pattern of certain macroinvertebrate taxa. By comparison, introduction of catfish within previously uninvaded localities provided evidence of direct catfish impact through elimination of conspicuous taxa. Acoustic telemetry was used to investigate catfish movement patterns within an invaded lentic habitat and provided evidence that habitat utilisation was non-random. The shallow and structured river mouth habitat, which was most utilised, was probably the most ideal for its breeding and feeding. This inferred potential overlap with native species and suggested the risk of predation and competitive interference. Catfish also exhibited both nocturnal and diurnal activity patterns that were probably related to feeding.
Keywords: Catfishes -- South Africa -- Eastern Cape; Biological invasions -- South Africa -- Great Fish River; Biological invasions -- South Africa -- Sundays River; Clarias gariepinus; Freshwater ecology